4-6m+5m=7

Simple and best practice solution for 4-6m+5m=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-6m+5m=7 equation:


Simplifying
4 + -6m + 5m = 7

Combine like terms: -6m + 5m = -1m
4 + -1m = 7

Solving
4 + -1m = 7

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1m = 7 + -4

Combine like terms: 4 + -4 = 0
0 + -1m = 7 + -4
-1m = 7 + -4

Combine like terms: 7 + -4 = 3
-1m = 3

Divide each side by '-1'.
m = -3

Simplifying
m = -3

See similar equations:

| (17x+8)=(13x+24) | | -10x+65=117 | | 14=3(n-4)-2n | | 2.4x=13.68 | | -3(1-8b)=-20 | | Cx=A-By | | (3m^4-2m^2+m)-(6m^3+8m^2+4m)+(m^2-m)= | | -1.3x=-10.4 | | 10-1/2x=27 | | 6+log(4)(4x)=8 | | 4n+8+7=25 | | -2(6x-2)=-68 | | 2/3x+1/2=5/2 | | 3(-4x+7)=-15 | | 3(-3m+4)=10-7m | | -2(x+2)-5=2+3 | | 0.4-0.5=0.3+8 | | 17+x=5x-6 | | (26x+22)=(38x-14) | | 7x/3-3x/10 | | -4(5x-6)=-6 | | -3(4v+4)+3v=-48 | | 4x^2/54=2/3 | | 4x-7=x+5-x | | 3x+3+x+11=90 | | X=-8+.40y | | -3(5x-4)=-33 | | 3(-5x-7)=-3(x-7)-6x | | 180-x+90-x=160 | | 2n-(3n-8)=2 | | -5-7x=-60 | | x-y/2 |

Equations solver categories